Menyikapi Preferensi Masyarakat Pondok Benda Pamulang Dalam Pemilihan Obat Flu Berdasarkan Iklan Dengan Bijak - Ainun Wulandari; Amelia Febriani; Teodhora Teodhora; Vilya Syafriana; Ika Maruya Kusuma; Hervianti Nurfitria Nugrahani; Fathin Hamida; Putu Rika Veryanti; Saiful Bahri; Refdanita Refdanita; Lili Musnelina; Pratiwi Ally Florentina (Pakis Journal Institute, 2024)
Flu is an upper respiratory tract infection that is often treated with various flu medications on the market and promoted through various media, especially television. This research aims to understand people's preferences for flu medicine in Pondok Benda Pamulang, South Tangerang. Through group discussions and delivery of educational materials, this study found that price, quality, and brand trust factors influenced the choice of flu medication. The results show an increase in public knowledge about flu and its treatment. The attractiveness of flu medicine advertisements is important in influencing consumer behavior. The right use of endorsers and advertising frequency can increase the effectiveness of advertising in mass media. This study provides insight into the importance of education in forming wise health decisions and provides a better understanding of people's preferences for cold medicines.